2023
DOI: 10.3390/ijms24076298
|View full text |Cite
|
Sign up to set email alerts
|

Cheminformatics-Based Study Identifies Potential Ebola VP40 Inhibitors

Abstract: The Ebola virus (EBOV) is still highly infectious and causes severe hemorrhagic fevers in primates. However, there are no regulatorily approved drugs against the Ebola virus disease (EVD). The highly virulent and lethal nature of EVD highlights the need to develop therapeutic agents. Viral protein 40 kDa (VP40), the most abundantly expressed protein during infection, coordinates the assembly, budding, and release of viral particles into the host cell. It also regulates viral transcription and RNA replication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 259 publications
0
11
0
Order By: Relevance
“…The natural sources of the nine potential lead compounds were investigated from various databases, including ZINC15 [ 163 ], PubChem [ 164 , 165 ], ChEMBL [ 166 , 167 , 168 ], LOTUS [ 169 ], KNApSAcK [ 170 , 171 ], Natural Product Activity and Species Source (NPASS) [ 172 ], and Indian Medicinal Plants, Phytochemistry And Therapeutics (IMPPAT) [ 173 ] as previously conducted [ 174 ]. The pharmacological activities of the plant sources were also probed from the existing literature.…”
Section: Resultsmentioning
confidence: 99%
“…The natural sources of the nine potential lead compounds were investigated from various databases, including ZINC15 [ 163 ], PubChem [ 164 , 165 ], ChEMBL [ 166 , 167 , 168 ], LOTUS [ 169 ], KNApSAcK [ 170 , 171 ], Natural Product Activity and Species Source (NPASS) [ 172 ], and Indian Medicinal Plants, Phytochemistry And Therapeutics (IMPPAT) [ 173 ] as previously conducted [ 174 ]. The pharmacological activities of the plant sources were also probed from the existing literature.…”
Section: Resultsmentioning
confidence: 99%
“…Energy decomposition per residue is a measure of the energy each residue in a protein‐ligand complex contributes to ligand interaction with a receptor [84] . Residues that contribute energy less than −5 kJ/mol or greater than 5 kJ/mol have been reported to be critical residues in the ligand interaction with a receptor [85] . For the NRP‐1‐CNP0435132 complex, Asp320 contributed 5.8 kJ/mol, implying its crucial role in ligand binding to NRP‐1 (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…[84] Residues that contribute energy less than À 5 kJ/mol or greater than 5 kJ/mol have been reported to be critical residues in the ligand interaction with a receptor. [85] For the NRP-1-CNP0435132 complex, Asp320 contributed 5.8 kJ/mol, implying its crucial role in ligand binding to NRP-1 (Figure S2). This corroborates earlier studies where Asp320 was reported as a critical residue in the ligand binding of NRP-1.…”
Section: Molecular Mechanics-poisson Boltzmann Surface Area (Mm-pbsa)...mentioning
confidence: 99%
“…Previous studies have shown that AutoDock Vina can distinguish between active and non-active binders with an AUC of ROC curves ranging between 0.7 and 0.99. AutoDock Vina has also been shown to successfully predict the binding pose of ligands in the binding pocket of proteins [ 52 , [53] , [54] , [55] ].…”
Section: Methodsmentioning
confidence: 99%